Agama sebagai Idola Publik dan Urgensi Teologi Harmoni - Rori Prima Dani Simbolon (Sekolah Tinggi Katolik Touye Paapaa Deiyai, 2026)
This article aims to examine the concept of “religion as an idol of the mind” in the thought of Francis Bacon and to propose a theology of harmony as a solution to the issue of religious diversity in Indonesia. The phenomenon of violence and intolerance in the name of religion remains a serious problem; research by the SETARA Institute has documented more than two thousand violations of religious freedom over the past decade, reflecting how religion often shifts from being a source of peace to a justification for destructive actions. Within the Baconian framework, idols of the court refer to prejudices formed through external influences that hinder the attainment of objective knowledge. When religion is co-opted by these forces, it transforms into an idol that shackles rationality and fuels fanaticism. This study further identifies nihilism as the deepest epistemological root of violence committed in the name of religion in Indonesia. This paper employs a qualitative method with a literature review approach to sources in philosophy, theology, and the sociology of religion. Based on this diagnosis, this study proposes a theology of harmony as an alternative approach that emphasizes authentic interfaith dialogue, the elimination of self-prejudice in line with Bacon’s inductive method, and a balance between religious belief and social life. Harmony theology, rooted in Indonesia’s local wisdom (Bhinneka Tunggal Ika and Pancasila), is expected to serve as the foundation for critical rationality in religious practice, while simultaneously fostering the development of a peaceful, inclusive, and civilized ecosystem of religious diversity.